Adsorption of Organic Compounds by Carbon Nanomaterials in Aqueous Phase: Polanyi Theory and Its Application - Yang, Kun; Xing, Baoshan (Chemical reviews, 2010)
A discussion of adsorption of organic compounds by carbon nanoparticles in aqueous chemistry is presented. The theory, molecular structure and models behind the interactions are explored.